Partners contribute more to Public Goods than Strangers: Conditional Cooperation - Claudia Keser; Frans van Winden (Tinbergen Institute, 1997)
In a series of experiments, we compare a situation where the same group of four subjects plays 25 repetitions of a public good game (partners condition) to a situation where subjects play this game in changing group formations over 25 periods (strangers condition). We observe that, on aggregate over all periods, subjects in the partners condition contribute significantly more to the public good than subjects in the strangers condition. This difference is significant already in the first period. In the strangers condition, contributions show a continual decay, while in the partners condition, contributionsfluctuate on a relatively high level until they drastically decrease in the final periods. Our tentative explanation is that subjects' behavior in the public good situation represents conditional cooperation, characterized by both future-oriented and simple reactive behavior. With this interpretation, we are able to explain the observed differences between the twoconditions.
Keywords: 330; Experimental Economics; Public Goods; Öffentliche Güter; Test; Theorie